Acid Fly or Paederus Dermatitis Among Foreign Medical Students Residing in Institutional Hostels in Rangpur, Bangladesh - Mehedi, Kamran; Rahman, Motiur; Shamsuzzman, Md; Imran, Shah Md Ahasanul; Afrose, Tanzina (Journal of Rangpur Medical College, 2026)
Background: Paederus dermatitis is a form of irritant contact dermatitis triggered by pederin, a toxin released when rove beetles are crushed against the skin. Outbreaks of this condition are frequently observed in residential institutions, particularly during rainy seasons. Objective: The study utilized line-listing to summarize cases by person, place, and time, supplemented by environmental walk-through assessments to identify risk factors. Methods: We performed a descriptive cross-sectional study of an outbreak among foreign medical students residing in three hostels at Rangpur Community Medical College (RCMC) in Bangladesh, covering the period from January to December 2025. Results: A total of 76 clinical cases and 79 attack episodes were identified. The majority of affected students were Nepalese (34/76) and Indian (33/76), and female students accounted for 40 of the 76 cases. Clustering was evident at the room level, with 13 rooms reporting two or more cases, and 91.1% (72/79) of attack episodes occurred during the monsoon months of July and August. Among 74 cases with available risk-factor data, the most frequently documented associated factors were seasonal occurrence during the monsoon (72/74, 97.3%), sleeping with windows open (59/74, 79.7%), shared exposure within rooms (49/74, 66.2%), crushing the insect on the skin (48/74, 64.9%), and bed placement near windows (42/74, 56.8%). Conclusion: The outbreak demonstrated strong seasonality and room-level clustering. Preventing future occurrences requires synchronized environmental management and student awareness strategies intensified during the monsoon. J Rang Med Col.2026 Mar;11(1): 124-129